2003
DOI: 10.1097/00000542-200301000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Differentially Blocks Sensory Afferent Synaptic Transmission in Medial Nucleus Tractus Solitarius (mNTS)

Abstract: The authors conclude that ketamine inhibits postsynaptic -methyl-d-aspartate receptors and presynaptic afferent processes in medial nucleus tractus solitarius. Unexpectedly, capsaicin-sensitive (C-type), unmyelinated afferents are significantly more susceptible to block than capsaicin-resistant (A-type), myelinated afferents. This differentiation may be related to tetrodotoxin-resistant sodium currents. Since C-type afferents mediate powerful arterial baroreflexes effects, these differential actions may contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 46 publications
4
42
0
Order By: Relevance
“…Activation of NMDARs in glial cells seems unlikely because calcium rises in glial cells induced by visceral fibers stimulation are insensitive to NMDAR blockade (McDougal et al, 2011). Although part of excitatory synapses between visceral fibers and NTS neurons do not express synaptic NMDARs (Doyle and Andresen, 2001; Jin et al, 2003), they are present extrasynaptically. In addition, EC may diffuse over micrometric distances (Chevaleyre and Castillo, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of NMDARs in glial cells seems unlikely because calcium rises in glial cells induced by visceral fibers stimulation are insensitive to NMDAR blockade (McDougal et al, 2011). Although part of excitatory synapses between visceral fibers and NTS neurons do not express synaptic NMDARs (Doyle and Andresen, 2001; Jin et al, 2003), they are present extrasynaptically. In addition, EC may diffuse over micrometric distances (Chevaleyre and Castillo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although, the PPR and CV changes demonstrate that the LTD is expressed presynaptically, NMDARs could be located in the presynaptic or postsynaptic compartment. Monosynaptic responses elicited by solitary tract stimulation often lack an NMDA component, thereby suggesting that at least some NTS glutamatergic synapses are devoid of NMDARs (Doyle and Andresen, 2001;Jin et al, 2003). To determine whether NMDARs were located presynaptically or postsynaptically, we used a specific postsynaptic blockade of NMDARs.…”
Section: Ltd Induced By Lfs Requires Nmdars Not Located In the Postsymentioning
confidence: 99%
“…In previous studies, we have shown that ST afferent pathways arising from myelinated and unmyelinated neurons can be distinguished by their susceptibility to blockade by the TRPV (vanilloid receptor) agonist capsaicin Jin et al, 2003). Namely, EPSCs mediated by unmyelinated afferents are typically blocked, whereas EPSCs mediated by myelinated afferents are unaffected.…”
Section: Myelinated and Unmyelinated St Pathways Activate Cvlm-and Pvmentioning
confidence: 99%
“…For example, evidence from intracellular recordings in horizontal slices (22,34) (22,34,35). The exception is a small population of second order NTS neurons with apparently myelinated ST afferent innervation (36). Methods of approach are critical considerations for interpreting results and, clearly, alternative explanations are needed to account for NMDA receptor responses in the NTS.…”
Section: The Case For the Strong Synapsementioning
confidence: 99%
“…We began with the premise that peripheral cellular differences in cranial afferent neurons (e.g., at the nodose ganglion) are present in the central, presynaptic terminals of these same sensory neurons. The expectation (Figure 2) is that pathways through the NTS would be divided on the basis of afferent class (34,36,56).…”
Section: Cellular Basis Of Nts Neurotransmissionmentioning
confidence: 99%